Influence of employee satisfaction and job performance in a public entity in 2024 - Jesús, Carrasco Arroyo, Cristhian; Angeles, Esteves Suclupe, María De Los; Milagro, Mori Chavesta, Luz Del; Melissa, Perez Iman, Anyela; Margot, Segura Saldarriaga, Adriana (Edelweiss Applied Science and Technology, 2025)
The objective of the study is to determine the relationship between employee satisfaction and job performance of officials in a public entity in the Province of Ferreñafe in 2024, contributing to the SDG: Health and Well-being. The research is of a non-experimental design, with a quantitative and correlational approach. The sample of the study consists of 107 participants, including appointed employees in the public entity, contract employees for service provision, and both genders were considered. The instrument used was a questionnaire. As a result, it is observed that job satisfaction is significantly related to job performance. The research allows us to conclude that higher satisfaction notably improves the job performance of officials in the Public Entity of the Province of Ferreñafe.